Structural Properties of Synaptic Transmission and Temporal Dynamics at Excitatory Layer 5B Synapses in the Adult Rat Somatosensory Cortex - Rollenhagen, Astrid; Ohana, Ora; Sätzler, Kurt; Hilgetag, Claus C.; Kuhl, Dietmar; Lübke, Joachim H. R. (Frontiers in Synaptic Neuroscience, 2018)
Cortical computations rely on functionally diverse and highly dynamic synapses. How their structural composition affects synaptic transmission and plasticity and whether they support functional diversity remains rather unclear. Here, synaptic boutons on layer 5B (L5B) pyramidal neurons in the adult rat barrel cortex were investigated. Simultaneous patch-clamp recordings from synaptically connected L5B pyramidal neurons revealed great heterogeneity in amplitudes, coefficients of variation (CVs) and failures (F%) of EPSPs. Quantal analysis indicated multivesicular release as a likely source of this variability. Trains of EPSPs decayed with fast and slow time constants, presumably representing release from small readily releasable (RRP; 5.4 ± 1.24 synaptic vesicles) and large recycling (RP; 74 ± 21) pools that were independent and highly variable at individual synaptic contacts (RRP range 1.2-12.8 synaptic vesicles; RP range 3.4-204 synaptic vesicles). Most presynaptic boutons (~85%) had a single, but ~2-5fold larger pre- (0.29 ± 0.19 µm2) and postsynaptic density (0.31 ± 0.21 µm2), often perforated active zone (AZ) when compared with even larger CNS synaptic boutons. They contained 200-3400 vesicles (mean ~750). At the AZ, ~4 and ~12 vesicles were located within a perimeter of 10 nm and 20 nm, reflecting docked and readily releasable vesicles of the putative RRP. Vesicles (~160) at 30-200 nm matched our functional estimate of the RP; while the remaining constituted a presumed large resting pool. Multivariate analysis revealed two clusters of L5B synaptic boutons distinguished by the size of their resting pool. Our functional and ultrastructural analyses closely link stationary properties, temporal dynamics and endurance of transmission release to vesicular content and distribution within the presynaptic boutons suggesting that functional diversity of L5B synapses is enhanced by their structural heterogeneity.